Community migration as an additional branch of Migration Linguistics: Evidence from Borneo - McLellan, James (Journal of Modern Languages, 2025)
This paper is about migrations of communities within, into, and out of Borneo. It seeks to adding a further category, community migration, to the four original categories of labour, family, education, and forced migration proposed by Borlongan (2023). This underpins research within the sociolinguistic frameworks of Language Contact and Ecology of Language, from both historical and contemporary perspectives. The introduction provides historical background about the migration of Austronesian peoples from Taiwan through the Philippines to Borneo and beyond. The main section of the paper covers some more recent migrations within and around Borneo of both coastal Malay/Muslim and interior groups collectively termed “Dayak.” A particular focus is on the Iban community’s migration across Borneo and into Brunei and the linguistic and sociolinguistic consequences of this. The Iban are the largest indigenous ethnic group in the Sarawak region, Malaysia (28.8% of the state’s population, https://en.wikipedia.org/wiki/Demographics_of_Sarawak). Other community migrations discussed are those of the Kayan, Bidayuh, Berawan, and Belait/Lemeting groups. A tentative four-way classification of Borneo community migration strategies is proposed: migrate and maintain (e.g., Iban, Malay); migrate and conquer/occupy other communities’ territory => conquered, enslaved group shifts to conquering the group’s language (e.g., Kayan); migrate and diversify/shift (e.g., Bidayuh); and migrate and merge (e.g., Berawan, Belait/Lemeting). The conclusion of the article critically evaluates the notion of community migration, connecting this to Borlongan’s other categories. The relevance of the Language Contact and Ecology of Language frameworks to the study of Migration Linguistics in Borneo is also addressed.